Agile-Based Human Resource Management Application Development to Improve Efficiency and Effectiveness of Cargo Company Operations - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research aims to develop an Agile-based Human Resources (HR) management application to improve operational efficiency and effec-tiveness in a freight forwarding company. Problems faced by the com-pany include inefficient work schedule management, unstructured training, and ineffective performance evaluation. The research method involved four main stages, namely require: requirements planning, de-velopment, and application testing. In the requirement definition stage, interviews with company management and a survey of employees were used to understand the challenges faced and user expectations of the proposed solution. Next, in the planning stage, a detailed project plan and application specifications were created to guide the development. The development stage involved prototyping, application code devel-opment, and integration of application features. Finally, the application was tested through a series of functional tests, user trials, and perfor-mance tests to ensure the quality and performance of the application. The results show that the application can address the problems faced by the company well and meet user expectations. The contributions of this research are the development of applications that are to the needs of the company, the application of Agile methodology in the develop-ment of business applications, and the provision of a foundation for further research in the field of technology-based HR management.